The 8th World One Health Congress highlights - Hung Nguyen-Viet; Alonso, Silvia; Patel, Ekta; Bakri, A. (International Livestock Research Institute, 2024)
For the first time in Africa, more than 1400 leading experts in One Health science and policy gathered in Cape Town for the 8th World One Health Congress from 19–23 September 2024. There were 70 sessions and over 600 scientific posters were presented. Experts called for inclusion of the One Health concept in binding frameworks to achieve the Sustainable Development Goals.